Ecological reconstruction of a mixed Middle Triassic forest from Argentina - Brea, Mariana (2008)
The palaeoecology of an in situ Middle Triassic forest known as the Darwin Forest, from the Paramillo Formation of Argentina, is described based on palaeobotanical, sedimentological and spatial analyses. The palaeoforest grew on an andisol soil that developed on volcaniclastic floodplain deposits. The volcanic detritus and the rhythmic amalgamation of upper flow-regime tractional deposits overlying the andisol indicate that the forest was buried rapidly by a subaerial, cool and wet pyroclastic base surge flow. The plant community was reconstructed by quantitative mapping of the fossilized stumps integrated with taxonomic and sedimentological information. The Darwin Forest had a tree density of 427-759 per ha, with an upper stratum (20-26 m) of corystosperms and a second stratum (16-20 m) of conifers. Estimated biomass is equivalent to modern dry monsoonal forest. The understorey was composed of ferns (Cladophlebis spp.). Quantitative growth-ring analysis of Araucarioxylon protoaraucana suggests that these trees were evergreen and, together with vegetation structure and sedimentary data, indicate that the forest developed under dry, subtropical, strongly seasonal conditions.